Explaining Commodity Prices by a Cointegrated Time Series-Cross Section Model - Cornejo Tonnelier, Magdalena (2015)
This paper analyzes idiosyncratic and common determinants of commodity prices by adopting a time series-cross section approach. Different from the previous empirical literature, we allow for long-run and short-run effects, testing for cointegration and accounting for cross-dependence among different commodities. An automatic model selection algorithm is used to obtain a dominant congruent econometric model, selecting among many potential explanatory variables. As the effects of commodity prices? determinantsmay vary over time and across commodities and we are estimating single conditional models, poolability and exogeneity issues are also evaluated. Our results indicate that commodity price formation in the long run is determined by supply and demand factors, apart from the US exchange rate. We find significant effects of individual commodity production and the demand-pull of China?s economy. The economic growth of both emerging and developed countries as well as the dollar?s depreciation, inventory changes, and easier monetary policies also have significant short-run effects on real commodity prices.